The impact of pedagogical and ICT training in teachers’ approaches to online teaching and use of digital tools - Haarala-Muhonen, Anne; Myyry, Liisa; Pyörälä, Eeva; Kallunki, Veera; Anttila, Henrika; Katajavuori, Nina; Kinnunen, Päivi; Tuononen, Tarja (Frontiers in Education, 2023)
This study examines the relationship between teachers' pedagogical and ICT training, their approaches to online teaching and the use of digital tools. The participants were 265, teachers from the large multi-disciplinary university in Finland. The data was collected in May-June 2020 during the early stages of Covid-19 pandemic. The results showed that teachers used digital tools more for delivering information and less for activating students. The study revealed that pedagogical training enhanced teachers' learning-focused approach to online teaching and diverse use of digital tools. Contrary to expectations, teachers' ICT training was not related to the use of digital tools. Therefore, it is important to provide pedagogical training to support teachers in implementing teaching in diverse teaching-learning environments and enhance building an online teaching, in which digital tools are used to promote interaction in online environment.